(untitled) (Simbiótica. Revista Eletrônica, 2020)
This article aims to provide reflection, having as lens the practices used and developed during the pandemic period in which the AGENT COVID-19 spread in multiple directions shifting our daily lives, our routines, disincorporating ourselves from the world and establishing new languages, new behaviors imposing a new model of representation of the dimensions of reality. The synthesis attempted in this article could only be performed through a brief qualitative cartographic historiography committed to access to the force plan that responds to the transformation of the experience that offer us clues to walk in a beyond the science-implementation dichotomy following paths, implication in production processes, connection of networks or rhizomes. We conclude that we are not yet a new collective. We are individuals on our way to a group consciousness. For now, what’s happening in this pandemic is that we all run under the awning of a bar because it’s raining. Thus, the contribution of the pandemic, allows us to invent a new language, which leads us to establish a relationship with our territory and our culture in a fairer way, more connected with our nature, making an architectural design more compatible with our “topography”, with our culture, with the people of the place. Keywords: Pandemic; Covid-19; isolation; crisis.